Fighting African capital flight: Trajectories, dynamics, and tendencies - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (Financial Innovation, 2020)
This study provides a harmonization framework for common capital flight policies in Africa. It builds on evidence of persistent extreme poverty in the continent to assess how common measures can be adopted by sampled countries on one cause of extreme poverty: capital flight. The dataset is sub-divided into fundamental characteristics of African capital flight based on income levels, legal foundations, natural resources, political stability, regional proximity, and religious domination. The main finding shows that from a projection date of 2010, a feasible timeframe for harmonizing policies is between 2016 and 2023. This timeframe coincides with the beginning of the post-2015 agenda on sustainable development goals.
Keywords: C50; E62; F34; O19; O55; 650; Econometric modeling; Capital flight; Poverty; Africa